Territories, sports identities and cultural landscapes: Los lugares de la memoria de la Ciudad Deportiva Magdalena Mixiuhca - García Ayala, José Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The places of memory function as significant marks of a history reconstructed from the present, which make up different cultural landscapes, which are symbolic representations of territories such as the Ciudad Deportiva Magdalena Mixiuhca and its sports geosymbols. The objective is to understand from the Method of Deep Hermeneutics, the Theory of Complex Systems and Complex Thought, how these places of high significance of sport are fundamental in the transfer of meanings and emotions, which identify this physically and symbolically appropriate space. , concluding that this is because they trigger evocative memories of emblematic events that consolidate diverse collective identities.